1988
DOI: 10.1007/bf02623892
|View full text |Cite
|
Sign up to set email alerts
|

Liver epithelial cell migration induced by epidermal growth factor or transforming growth factor alpha is associated with changes in the gene expression of secreted proteins

Abstract: Rat liver epithelial cells are induced to migrate by epidermal growth factor (EGF) or transforming growth factor alpha (TGF-alpha) in serum-free medium supplemented with insulin. Immunohistological staining of the migration tracks containing laminin and fibronectin has allowed a quantitative analysis of the process. The growth factor-induced migration is relatively slow, but very efficient. Between 24 and 48 h after exposure to EGF (or TGF-alpha), 50 to 70% of the cells have migrated away from their site of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 33 publications
3
25
1
Order By: Relevance
“…TGF-f has been shown to modulate cellular production of matrix proteins, plasminogen activator, and plasminogen activator inhibitor (30,47), and EGF stimulates transcription of integrins in 3T3 fibroblasts (48). In rat liver epithelial cells, EGF-induced migration is associated with altered fibronectin and laminin gene expression (49), and ECM proteins appear to modulate migration (50). In addition, activation of fibronectin receptor function has been demonstrated in keratinocytes during cutaneous wound healing (5 1), and specific integrin subunits were detected in migrating, but not resting, keratinocytes (52).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-f has been shown to modulate cellular production of matrix proteins, plasminogen activator, and plasminogen activator inhibitor (30,47), and EGF stimulates transcription of integrins in 3T3 fibroblasts (48). In rat liver epithelial cells, EGF-induced migration is associated with altered fibronectin and laminin gene expression (49), and ECM proteins appear to modulate migration (50). In addition, activation of fibronectin receptor function has been demonstrated in keratinocytes during cutaneous wound healing (5 1), and specific integrin subunits were detected in migrating, but not resting, keratinocytes (52).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that rat liver epithelial cells induced to migrate by EGF deposit ECM migration tracks that contain FN as one of its components, and also synthesize increased amounts of the protein [4]. We now show that the induction of FN by EGF occurs shortly after exposure of the cells to the growth factor and is associated with an increase in the amount of mRNA for the cellular type of FN.…”
Section: Introductionmentioning
confidence: 50%
“…FN is also required for migration during development (e.g., neural crest cells [2]) and is involved in liver tissue repair [3] and liver cell migration [4]. From the single FN gene, up to 12 (rat [5]) or 20 (human [18]) variants can be derived by differential splicing of the primary transcript.…”
Section: Introductionmentioning
confidence: 99%
“…EGF-stimulated PAI-1 (earlier reported as EGF/TGFα-inducible protein EIP-1) synthesis is closely associated with EGF-induced cell migration in both normal and Ha-Ras-transformed liver epithelial cells (Bade and Feindler 1988;Manske, Feindler et al 1990;Seebacher, Manske et al 1992). …”
Section: Pai-1 Regulation By Egfmentioning
confidence: 97%
“…Thalacker and Nilsen-Hamilton 1987; Bade and Feindler 1988), and these proteins are deposited into the ECM migration tracks (Seebacher, Manske et al 1992). However, PAI-1…”
Section: Pai-1 Regulation By Egfmentioning
confidence: 99%